1999
DOI: 10.1086/300675
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Early Formation of Field Elliptical Galaxies

Abstract: We present the results of an HK' wide-field survey encompassing the Hubble Deep Field and its Flanking Fields. Our wide-field survey provides uniform coverage of an area 61.8 square arcmin to a depth equivalent to K=20.1 at 5-sigma. We have also imaged the Hubble Deep Field in HK', providing uniform coverage of an area 7.8 square arcmin to a depth equivalent to K=21.2 at 5-sigma. Using these data in combination with new deep UH 8K V and I imaging obtained on the CFHT, we find only a small population of objects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
187
3

Year Published

2000
2000
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(205 citation statements)
references
References 43 publications
15
187
3
Order By: Relevance
“…This CDF-N observation has also allowed us to place strong constraints on two potential extended X-ray-emitting systems, ClG 1236+6215 and VLA J123725+621128. Both systems lie at high redshift and, from their undetected status, may still be in the early stages of dynamical evolution, having not yet -Chandra ACIS-I adaptively smoothed soft-band contours of the undetected cluster of galaxies ClG 1236+6215 overlaid on the I-band image of Barger et al (1999). The properties of the image (e.g., contours and bar) are identical to those described in Fig.…”
Section: Basic Nature Of the Extended X-ray Sourcesmentioning
confidence: 80%
See 3 more Smart Citations
“…This CDF-N observation has also allowed us to place strong constraints on two potential extended X-ray-emitting systems, ClG 1236+6215 and VLA J123725+621128. Both systems lie at high redshift and, from their undetected status, may still be in the early stages of dynamical evolution, having not yet -Chandra ACIS-I adaptively smoothed soft-band contours of the undetected cluster of galaxies ClG 1236+6215 overlaid on the I-band image of Barger et al (1999). The properties of the image (e.g., contours and bar) are identical to those described in Fig.…”
Section: Basic Nature Of the Extended X-ray Sourcesmentioning
confidence: 80%
“…As a consistency check for the SExtractor photometry, we matched our sources to sources in the catalog of Barger et al (1999); we found good agreement, with 1 deviations of .0.25. As expected, the largest deviations were always near the detection threshold of the images.…”
Section: Optical Images and Photometrymentioning
confidence: 82%
See 2 more Smart Citations
“…Zepf 1998, Barger et al 1999, based on the very low surface density of EROs recovered in K-selected samples. However, others found results consistent with a constant comoving density, even up to z ∼ 2 (e.g.…”
mentioning
confidence: 99%